Experimental study on ultrasound-based underground pretreatment of mine water well - LI Ang; LÜ Luna; LÜ Wei; TIAN Shengqi; FAN Liuyi; SUN Jingxin; FENG Biye; YANG Jiakang; XUE Zhixuan (矿业科学学报)
The conventional pretreatment methods for mine water generally include coagulation, sedimentation (flotation), and filtration. However, large equipment footprint, long processing time and pollution from coagulants and flocculants have been limiting the further development of underground mine water treatment. In this light, we designed an underground mine water pretreatment device based on ultrasonic atomization for clarifying and pre-softening mine water so that the turbid mine water could be treated to meet the needs of underground production, firefighting, and dust reduction. We conducted indoor experiments on mine water clarification and pre-softening treatment using water and rock samples from the field mined-out area. The results show that: (1) This method can clarify black-gray turbid mine water with a large amount of solid impurities, effectively removing insoluble solid impurities in the water. (2) Ultrasonic atomization reduces the total hardness of the water by 72.24%. The milligram equivalent concentration of Ca2+ is reduced from 5.33 mg/L to 0.81 mg/L and the milligram equivalent concentration of Mg2+ drops from 5.23 mg/L to 2.13 mg/L, with little impact on pH. (3) The water from the mined-out area after ultrasonic atomization can meet the requirements of sprinkling in underground firefighting, spraying in dust reduction, the mining process of coal mining equipment, and the use of cooling water.